Photodynamic therapy associating Photogem (R) and blue LED on L929 and MDPC-23 cell culture - Dias Ribeiro, Ana Paula [UNESP]; Pavarina, Ana Claudia [UNESP]; Trindade, Flavia Zardo [UNESP]; Inada, Natalia Mayumi; Bagnato, Vanderlei Salvador; de Souza Costa, Carlos Alberto [UNESP] (Academic Press Ltd Elsevier B.V. Ltd, 2010)
To evaluate the cytotoxicity of PDT (photodynamic therapy) with Photogem (R) associated to blue LED (light-emitting diode) on L929 and MDPC-23 cell cultures, 30000 cells/cm(2) were seeded in 24-well plates for 48 h, incubated with Photogem (R) (10, 25 or 50 mg/l) and irradiated with an LED source (460 +/- 3 nm; 22 mW/cm(2)) at two energy densities (25.5 or 37.5 J/cm(2)). Cell metabolism was evaluated by the MTT (methyltetrazolium) assay (Dunnet's post hoc tests) and cell morphology by SEM (scanning electron microscopy). Flow cytometry analysed the type of PDT-induced cell death as well and estimated intracellular production of ROS (reactive oxygen species). There was a statistically significant decrease of mitochondrial activity (90% to 97%) for all Photogem (R) concentrations associated to blue LED, regardless of irradiation time. It was also demonstrated that the mitochondrial activity was not recovered after 12 or 24 h, characterizing irreversible cell damage. PDT-treated cells presented an altered morphology with ill-defined limits. In both cell lines, there was a predominance of necrotic cell death and the presence of Photogem (R) or irradiation increased the intracellular levels of ROS. PDT caused severe toxic effects in normal cell culture, characterized by the reduction of the mitochondrial activity, morphological alterations and induction of necrotic cell death.
Keywords: cytotoxicity; fibroblast; haematoporphyrin derivative; odontoblast; photodynamic therapy